QT Prolongation in Cancer Patients - Kim, Peter; Masha, Luke; Olson, Amanda; Iliescu, Cezar; Karimzad, Kaveh; Hassan, Saamir; Palaskas, Nicolas; Durand, Jean-Bernard; Leung, Cheuk Hong; Lopez-Mattei, Juan (Frontiers in Cardiovascular Medicine, 2021)
Background: QT prolongation and torsades de pointes pose a major concern for cardiologists and oncologists. Although cancer patients are suspected to have prolonged QT intervals, this has not been investigated in a large population. The purpose of this study was to analyze the QT interval distribution in a cancer population and compare it to a non-cancer population in the same institution. Methods: The study was a retrospective review of 82,410 ECGs performed in cancer patients (51.8% women and 48.2% men) and 775 ECGs performed in normal stem cell donors (47.9% women and 52.1% men) from January 2009 to December 2013 at the University of Texas MD Anderson Cancer Center. Pharmacy prescription data was also collected and analyzed during the same time period. Correction of the QT interval for the heart rate was performed using the Bazett and Fridericia formulas. Results: After QT correction for heart rate by the Fridericia formula (QTcF), the mean and 99% percentile QTc for cancer patients were 414 and 473 ms, respectively. These were significantly longer than the normal stem cell donors, 407 and 458 ms, p < 0.001, respectively. Among the cancer patients, the QTc was longer in the inpatient setting when compared to both outpatient and emergency center areas. The most commonly prescribed QT prolonging medications identified were ondansetron and methadone. Conclusion: Our study demonstrates significantly longer QTc intervals in cancer patients, especially in the inpatient setting. Frequently prescribed QT prolonging medications such as antiemetics and analgesics may have a causative role in QT prolongation seen in our cancer hospital.